2019
DOI: 10.23851/mjs.v30i1.146
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Heat and Momentum Fluxes Over Baghdad City

Abstract: In this study heat and momentum fluxes have been determined at Al-Mustansiriyah University, Baghdad, Iraq, by using eddy correlation method. It is one of the methods which determines heat and momentum fluxes and it is considered direct and accurate. This method depends on high response instruments like Ultrasonic Anemometer (model: 1590- PK- 020) which is used in this study. Observation period is about 53 days for 24 hours in months June, July and August from 15/06/2016 to 06//08/2016 and the observations incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The coupled method was used to solve the Reynoldsaveraged Navier-Stokes equations (RANS), continuity equation, and energy equation, which represent conservation of momentum (product between a particle's mass and velocity (kg × m/s) (Mehson and Hassoon, 2019), conservation of mass, and conservation of energy (the energy of interacting objects or molecules in a closed system remains constant) (Fattah and et al, 2021), respectively. As well as to solve the three-dimensional equations of turbulent kinetic energy (It is particularly significant in microfluid dynamics since it has a direct bearing on momentum transfer via the boundary layer (Mohammed, 2016) and turbulent dissipation (Thomson, 1971).…”
Section: Solution Methodsmentioning
confidence: 99%
“…The coupled method was used to solve the Reynoldsaveraged Navier-Stokes equations (RANS), continuity equation, and energy equation, which represent conservation of momentum (product between a particle's mass and velocity (kg × m/s) (Mehson and Hassoon, 2019), conservation of mass, and conservation of energy (the energy of interacting objects or molecules in a closed system remains constant) (Fattah and et al, 2021), respectively. As well as to solve the three-dimensional equations of turbulent kinetic energy (It is particularly significant in microfluid dynamics since it has a direct bearing on momentum transfer via the boundary layer (Mohammed, 2016) and turbulent dissipation (Thomson, 1971).…”
Section: Solution Methodsmentioning
confidence: 99%
“…On the eastern side of Baghdad in this location, it mostly consists of various roughnesses from 3-meter-tall houses to 30-meter-tall buildings like government offices. Trees and about 80% of buildings surround the study site [2].…”
Section: The Locationmentioning
confidence: 99%
“…), flux formulas in the atmosphere must be transformed into abstract kinematic forms to become heat flux movement by dividing by the density of moist air. [2] Quantitative amounts are transferred across time and space as a result of fluid movement. It is common knowledge that flow, or fluid movement, consists of two fundamental components: turbulence and rate, and it has been demonstrated that heat is transferred to and from the Earth in the boundary layer, particularly the surface layer, by turbulence [3].…”
Section: Introductionmentioning
confidence: 99%